España, la República de orden - Pilar Mera Costas (Casa de Velázquez, 2020)
«For all those who look at the situation serenely, the Republic and Spain are one and the same thing». With these words, Manuel Portela Valladares, Minister of the Interior, claimed the peaceful and orderly Republic on the eve of April 14, 1935. Months after the events of October, while the country was recovering little by little the political normality, the national holiday offered an occasion to celebrate the ideal of liberal civic homeland. The objective of this article is to analyze what role the commemoration of Republic Day played in the national discourse of the liberal republicans, how the planning and ritualization of the National Day reflected his conception of public order, and to what extent their project had a social projection. I will study the planning and development of the celebrations throughout the country. I will analyze the use of national symbols, political speeches, participation of law enforcement forces in military parades, the degree of social penetration of activities and the presence of children in the party.